Collaborating with other disciplines: best practice for legal clinics - a case study of the women’s law clinic, University of Ibadan Nigeria (2013)
There is a gradual shift in research towards a multi-disciplinary approach. This paradigm move is in compliance with globalization. According to Carla Mariano, the human service professions are facing problems so complex that no one discipline can possibly respond to them effectively. It has been noted that many clients in the Women’s Law Clinic (WLC) of the University of Ibadan not only have problems tagged as legal, but problems closely related to other disciplines such as psychology, sociology, medicine, counselling and social works. It was therefore so obvious that the clinic was not an island; it could not exist all alone and effectively find a holistic solution to the all embracing problems presented by the clients. The clinic therefore partnered with other departments/units to achieve its goals.